Preservation mechanism of Boletus edulis enzymatic hydrolysate on refrigerated yak meat: synergistic effect of microbial community succession and protein expression regulation - Ningjing Guo; Xue Li; Changling Lian; Jian Wang; Longquan Xiao; Yiming Zhou; Xiang Li; Xiaowei Li; Jingxian Yang (Food Control, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Formation of ι-carrageenan-mediated complex: Enhancing thermal stability of α-amylase inhibitor from white kidney bean - Xine Huang; Yizhou Xiang; Xiaoning Zhu; Chenjuan Zeng; Liang Zou; Lei Wang; Changling Wu; Xingquan Liu; Zisheng Luo; Li Li (Food Hydrocolloids, 2026)

Green and efficient maize varieties synergize global yield and nitrogen sustainability - Xun Wei; Yulong Yin; Xueqin Zhu; Ziwen Li; Zhenying Dong; Yan Long; Yanbo Wang; Jiuran Zhao; Changling Huang; Xingming Fan; Huabang Chen; Pervez H. Zaidi; et al. (Science Bulletin, 2026)

Fragility analysis of reinforced concrete column subject to blast loads induced by fireball surface instabilities - Ye Hu; Yanchao Shi; Jian Cui; Changling Xie; Li Chen; Kaiwei Lu; Runjie Cai (Engineering Structures, 2026)

Natural gas hydrate morphology evolution and resistivity response during thermal dissociation in porous media - Yongge Liu; Yipu Li; Jianxin Liu; Jian Hou; Zezheng Sun; Bin Fang; Yuechao Zhao; Qingjun Du; Yunkai Ji; Changling Liu; Bei Wei; Zhangxing Chen (Chemical Engineering Journal, 2026)

Analysis of shearing behavior in hydrate-bearing sediments from a micromechanical perspective: A DEM simulation study - Jiawei Zhang; Yongchao Zhang; Lele Liu; Lei Wang; Yanlong Li; Yunkai Ji; Bo Zou; Changling Liu (Geomechanics for Energy and the Environment, 2026)

Xerophilusin B attenuates wear particle: associated osteolysis by inhibiting NF-κB signaling and restoring osteoblast–osteoclast coupling - Hui Shi; Qian Meng; Tao Meng; Changling Du; Chuang Xu; Heng Cao; Kefan Zhang; Jian Li (Journal of Molecular Histology, 2026)

Molecular simulation of hydrocarbon adsorption in transition-metal-modified zeolites for controlling natural gas engine cold-start emissions - Yuyu Li; Chuanfu Kou; Jiaqiang E; Dezhong Ning; Yan Tan; Changling Feng; Chen Xiang (Fuel, 2026)

Network pharmacology research integrating LC–MS/MS, machine learning, molecular docking, and dynamics simulation: key biomarkers and potential mechanisms of Phellinus igniarius against prostate cancer - Zixuan Ren; Xiaohong Liu; Jihang Zhang; Min Song; Qingwen Yang; Changling Li; Deshan Liu (In Silico Pharmacology, 2026)

Vertical zonation and interaction patterns of heterotrophic protists in the Bay of Bengal and Eastern Indian Ocean - Laxman Pujari; Qi Qiao; Sujata Nilajkar; Ting Gu; Danyang Li; Yiyan Guo; Xuelei Zhang; Lin Liu; Changling Ding; Jun Sun (Marine Pollution Bulletin, 2026)

Interannual variability of surface urban Heat Islands across global cities: Patterns and climatic drivers - Ruihan Qiu; Qingming Zhan; Shiqi Tu; Changling Li (Urban Climate, 2026)

Development of high-performance organic solvent-resistant thin-film composite membranes for small molecule separation via an enhanced interfacial polymerization strategy - Changling Yu; Ziye Wang; Biao Ma; Jiaxin Zhang; Zhenlong Wang; Honglin Huang; Song Cao; Guangyu Li; Chao Wu; Yuanzhen Li (Journal of Environmental Chemical Engineering, 2026)

Evolution characteristics of methane concentration and microscopic formation mechanisms of methane hydrate: Insights from in-situ Raman spectroscopy - Xiaoqian Qiu; Yunkai Ji; Qingguo Meng; Qingtao Bu; Xiluo Hao; Changling Liu; Yapeng Zhao; Jianye Sun; Qi Li; Gaowei Hu (Gas Science and Engineering, 2026)

Ultrasonic-assisted deep eutectic solvents extraction of saponins from Strobilanthes sarcorrhiza: Process optimization and mechanistic insights - Peng Wang; Kaijun Wang; Tiantian Li; Shilin Zhang; Jiang Wu; Fenghua Wu; Guanyu Fang; Changling Wu; Xingquan Liu (Chemical Engineering Journal, 2026)

Experimental and hypoplastic model investigation of frozen soil mechanics: Integrating confining pressure, temperature, and ice content effects - Jiawei Zhang; Yongchao Zhang; Ke Ke; Lilin Li; Yanlong Li; Lele Liu; Changling Liu; Nengyou Wu (Cold Regions Science and Technology, 2026)

Advances in emerging two-dimensional nanomaterials: Design strategies, structural engineering, and applications in food - Wanfeng Wu; Tuck-Whye Wong; Xingquan Liu; Changling Wu; Nannan Dong; Mengyun Tu; Jingjing Zhou; Yaoqi Zhang; Mengfei Mao; Tiefeng Li; XuXu Yang; Li Li (Trends in Food Science & Technology, 2025)

Regulation of aerobic methane oxidation by methane concentration: insights from cultivation experiments - Qikun Tian; Yu Zhen; Jing Li; Xiaoqing Xu; Changling Liu (Acta Oceanologica Sinica, 2025)

Effect of chitosan coating on the characterization and stability of the CPH liposomes - Peng Wang; Shuqing Zhu; Qiaonan Zhu; Xuan Yang; Changling Wu; Kaiyun Liang; Zhehua He; Weihong Min; Xingquan Liu; Weirong Li; Fenghua Wu (Journal of Food Engineering, 2025)

Identification of stable reference genes for qPCR analysis of gene expression in Oocystis borgei under various abiotic conditions - Ning Zhang; Jiajia Ren; Ting Hong; Zhongdian Dong; Feng Li; Yulei Zhang; Xianghu Huang; Changling Li; Zhangxi Hu (Algal Research, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Experimental Analysis of Resistivity Logging Response of Marine Gas Hydrate Reservoirs - Qiang Chen; Chengfeng Li; Hongbin Wang; Changling Liu; Qingtao Bu; Jianye Sun; Jiangong Wei; Beibei Kou (Journal of Ocean University of China, 2025)

Dependence of the hydrate-based CO2 storage characteristics on sand particle size and clay content in unconsolidated sediments - Jiaxian Wang; Yunkai Ji; Changling Liu; Fulong Ning; Qingguo Meng; Yapeng Zhao; Jing Li; Zhun Zhang; Yongchao Zhang; Feng Cai (Chemical Engineering Journal, 2024)

Fungal fermentation improves the nutritional quality, flavor characteristic and physicochemical property of highland barley bran - Yongzhu Zhang; Mingxin Liu; Fenghua Wu; Jinmei Li; Fidelis Azi; Ke Yu; Zhiping He; Peng Wang; Changling Wu; Baiyi Lu; Xingquan Liu (Journal of Cereal Science, 2024)

Analysis of permeability anisotropy of marine hydrate-bearing sediments using fractal theory combined with X-CT - Zhun Zhang; Zikun Li; Chengfeng Li; Zhuo Zhang; Changling Liu; Wanjun Lu; Fulong Ning (Ocean Engineering, 2024)

Effects of salinity on the growth, physiological and biochemical components of microalga Euchlorocystis marina - Yao Pan; David Kwame Amenorfenyo; Mingbiao Dong; Ning Zhang; Xianghu Huang; Changling Li; Feng Li (Frontiers in Marine Science, 2024)
Euchlorocystis marina , a new marine species of the genus Euchlorocystis discovered in 2022, has the potential to improve the water quality in mariculture ponds. However, the effects of salinity on the growth, physiology, and biochemical composition of these algae are not well understood. In this study, changes in physiological and biochemical indices such as cell density, photosynthetic pigment, polysaccharide, and lipid content of E. marina under different salinity treatments were analyzed. The results showed that the highest cell density was observed at a salinity of 15‰. The lowest photosynthetic pigment content was observed at a salinity of 60‰, and the highest polysaccharide and lipid content was observed at a salinity of 60‰. These results indicated that lower salinity was more conducive to E. marina reproduction and growth. E. marina can accumulate polysaccharides and lipids in high salinity environments. This study provides new information for understanding the salinity adaptation strategies of E. marina and has practical significance for its development and utilization.

Correction to: A Transcriptome Analysis of Neural Tissue of Litopenaeus vannamei After Acute Exposure to Alexandrium pacificum - Huijie Yang; Xianghu Huang; Yukun Ma; Zhangxi Hu; Ning Zhang; Changling Li; Yulei Zhang (Journal of Ocean University of China, 2024)

The pore-structure characteristics of foraminiferal shells and their relations with natural gas hydrate formation in the marine sediments - Yongchao Zhang; Lele Liu; Jing Li; Qiang Chen; Chengfeng Li; Jianye Sun; Changling Liu (Gas Science and Engineering, 2024)

A Transcriptome Analysis of Neural Tissue of Litopenaeus vannamei After Acute Exposure to Alexandrium pacificum - Huijie Yang; Xianghu Huang; Yukun Ma; Zhangxi Hu; Ning Zhang; Changling Li; Yulei Zhang (Journal of Ocean University of China, 2024)

Survey of the biogenic amines in typical foods commonly consumed from the Chinese market - Xuan Zhang; Changling Fang; Xiaoyi Lou; Feng Han; Siman Li; Yongfu Shi; Dongmei Huang (Food Control, 2024)

Simultaneous Determination of Seven Pyrethroid Pesticide Residues in Aquatic Products by Gas Chromatography - Changling Fang; Xiaoyi Lou; Xuan Zhang; Siman Li; Yunyu Tang; Yongfu Shi; Dongmei Huang (Fishes, 2024)
Aquatic products are good sources of essential nutrients, but the presence of pyrethroids (PYRs) as contaminants may pose risks to consumer health as the intricate matrices of PYRs usually obstruct chemical hazard detection. In this study, a gas chromatographic method was established and validated for simultaneously detecting residues of seven PYRs (cyhalothrin, permethrin, cyfluthrin, cypermethrin, tau-fluvalinate, fenvalerate, deltamethrin) in aquatic products. The aim of this method was to assess better the potential risks of pesticide residues in aquatic products. The PYRs in aquatic products were extracted with acetonitrile, purified with n-hexane saturated with acetonitrile, and cleaned up on a Cleanert® Alumina N column. Statistical analysis and orthogonal array experimental design were used to optimize the key parameters. To validate the proposed method, commonly consumed aquatic products (such as carp, crucian carp, whiteleg shrimp, river crab, sea cucumber, and scallop) were obtained from local supermarkets in Shanghai. Satisfied linearity of the calibration curves was achieved in a matrix-matched standard solution, with a correlation coefficient (R2) larger than 0.995. The average recoveries at five fortification levels varied from 77.0% to 117.2%, with relative standard deviations (RSDs) below 11.1%. Concerning electron capture detection, the limits of detection (LOD) and limits of quantification (LOQ) were 2.0–5.0 µg/kg and 5.0–10.0 µg/kg, respectively. These results demonstrate the high stability and sensitivity of this method for simultaneously detecting PYRs in aquatic products, having great practicability and which can be popularized easily.

Effects of exercise-targeted hippocampal PDE-4 methylation on synaptic plasticity and spatial learning/memory impairments in D-galactose-induced aging rats - Yu Jin; Xue Li; Changling Wei; Qiongjia Yuan (Experimental Brain Research, 2024)
Physical exercise reduces the effects of aging and cognitive decline by improving synaptic plasticity and spatial learning. However, the underlying neurobiological mechanisms are unclear. A total of 45 Male SPF Sprague–Dawley rats were acclimatized and then allocated into three groups, 15 in each group: the saline control (DC) group, D-gal-induced aging (DA) group, and D-gal-induced aging + exercise (DE) group. Six weeks of intraperitoneal injections of D-gal at a concentration of 100 mg/kg body weight/d was injected to establish model of aging in the DA and DE groups. Morris water maze test was implemented to evaluate the hippocampus related cognition. SOD activity and MDA was tested to assess the aging in all groups. H&E and Nissl staining was used to observe the histopathological changes of hippocampal neurons in aging rats. Quantitative real-time polymerase chain reaction, western blotting and immunofluorescence staining techniques were used to investigate the expression of synaptic genes and proteins in the hippocampus. Massarray methylation system was employed to measure the PDE-4 gene methylation level in rat hippocampal tissues. Our results demonstrated that exercise intervention improves cognitive function in D-gal-induced aging rats. The methylation of CpG sites in PDE-4 in the hippocampus was significantly increased. The physical exercise significantly increased PDE-4 gene methylation and effectively decreased PDE-4 gene and protein expression. These beneficial behavioral and morphological effects were attributed to PDE-4 methylation, which was activated cAMP/PKA/CREB pathway and improved synaptic plasticity. Exercise induced PDE-4 methylation is key mechanism underpinning the amelioration of learning/memory impairment, suggesting the potential efficacy of physical exercise training in delaying brain aging.

Evaluation of the Shallow Gas Hydrate Production Based on the Radial Drilling-Heat Injection-Back Fill Method - Qiang Chen; Yizhao Wan; Nengyou Wu; Jianye Sun; Jian Wang; Changling Liu; Yanlong Li; Chengfeng Li; Gaowei Hu (Journal of Ocean University of China, 2024)

Characteristics of arsenic speciation in mainly cultured shellfish from Sanmen Bay, Zhejiang Province, China - Maoxia Ran; Yongfu Shi; Di Wu; Hongli Ye; Dongsheng Feng; Dongmei Huang; Siman Li; Changling Fang (Marine Pollution Bulletin, 2023)

Evolution of the Tóxicos en Levadura 63 (TL63) gene family in plants and functional characterization of Arabidopsis thaliana TL63 under oxidative stress - Peng Li; Yuxin Zhang; Changling Zhao; Min Jiang (Planta, 2023)

Hydrophyte Debris Induced Sedimentary Phosphorus Release in Tuojiang Rivers, China - Changling Liu; Xianfan Yuan; Yuqiong Li; Zhong Yang (Bulletin of Environmental Contamination and Toxicology, 2023)

Elastic wave velocity of marine sediments with free gas: Insights from CT-acoustic observation and theoretical analysis - Jie Chen; Gaowei Hu; Qingtao Bu; Nengyou Wu; Changling Liu; Qiang Chen; Chengfeng Li; Yizhao Wan; Zihao Wang; Wengao Zhao; Jiale Kang; Jiafang Xu (Marine and Petroleum Geology, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Hydrate formation and distribution within unconsolidated sediment: Insights from laboratory electrical resistivity tomography - Yanlong Li; Nengyou Wu; Changling Liu; Qiang Chen; Fulong Ning; Shuoshi Wang; Gaowei Hu; Deli Gao (Acta Oceanologica Sinica, 2022)

Effect of Hydrate Microscopic Distribution on Acoustic Characteristics during Hydrate Dissociation: An Insight from Combined Acoustic-CT Detection Study - Qingtao Bu; Tongju Xing; Chengfeng Li; Jinhuan Zhao; Changling Liu; Zihao Wang; Wengao Zhao; Jiale Kang; Qingguo Meng; Gaowei Hu (Journal of Marine Science and Engineering, 2022)
Geophysical detection techniques are important methods in marine gas hydrate exploration and monitoring, because the small-scale distribution of hydrates has a large impact on the wave velocity. The acoustic response characteristics of hydrate micro-distributions have strong significance for monitoring the hydrate dissociation process. In this paper, experiments simulating the hydrate dissociation process were carried out in a self-developed experimental device combining X-ray computed tomography (X-CT) scanning and ultrasonic detection, which allowed the acoustic wave characteristics and X-CT scanning results to be simultaneously obtained during the hydrate dissociation process. This study found that the hydrate dissociation stage is divided into three stages. The hydrate begins to dissociate at spots where it comes into touch with sand particles early in the dissociation process. The main factor affecting the acoustic wave velocity of hydrates in this stage is changes in the microscopic distribution of hydrate. In the middle stage, a large amount of hydrate decomposes, and the main factor affecting the acoustic wave velocity of hydrate in this stage is the change in hydrate content. In the later stage of hydrate dissociation, the hydrate distribution pattern consists mainly of the pore-filling type, and the hydrate micro-distribution at this stage is the main factor affecting the acoustic wave velocity. This study will be of great significance for understanding the microscopic control mechanism of hydrate reservoir geophysical exploration.

Effects of Nitrogen and Light Intensity on the Astaxanthin Accumulation in Motile Cells of Haematococcus pluvialis - Feng Li; Minggang Cai; Yanqi Wu; Qingsheng Lian; Zuyuan Qian; Jiansen Luo; Yulei Zhang; Ning Zhang; Changling Li; Xianghu Huang (Frontiers in Marine Science, 2022)
The dietary supplementation of Haematococcus pluvialis is a natural, safe, and sustainable method for fish pigmentation. However, astaxanthin-rich H. pluvialis cysts have a poor effect in pigmenting salmonid flesh due to their rigid and thick cell wall. H. pluvialis thin-walled motile cells have recently attracted attention due to their potential advantages in maintaining compound stability, easy digestion, enhancing the bioavailability of carotenoids, and reducing production costs. This study aimed to investigate the effect of various nitrogen concentrations and light intensities on astaxanthin production in motile cells. We first investigated the effect of four different concentrations of nitrogen on astaxanthin accumulation in motile cells. According to the results, the motile cells had the highest astaxanthin concentration and content under the 0 N condition. Then, we compared the differences in astaxanthin production in motile cells under three different light intensities under 0 N conditions. The results showed that after four days of treatment, the protoplasts of the motile cells in the medium light (ML) group and the high light (HL) group had distinct granularity. The cell mortality rate in the HL group reached more than 15%, which was significantly higher than that in the low light (LL) and ML groups, indicating that high light intensity was not suitable for inducing motile cells to accumulate astaxanthin. There were no significant differences between the LL and ML groups in astaxanthin content, motile cells percentage, and cell mortality rate. Considering these indicators, we recommended inducing motile cells to produce astaxanthin under low light conditions because it is more economical in terms of electricity consumption. This study added to the knowledge that nitrogen and light affects the accumulation of astaxanthin in H. pluvialis motile cells. The results would help determine the optimal nitrogen and light conditions in astaxanthin production from motile cells.

Research Progress on Global Marine Gas Hydrate Resistivity Logging and Electrical Property Experiments - Qiang Chen; Nengyou Wu; Changling Liu; Changchun Zou; Yang Liu; Jianye Sun; Yanlong Li; Gaowei Hu (Journal of Marine Science and Engineering, 2022)
Natural gas hydrate is widely spread in marine environments around the world. It has great energy potential due to its high methane gas content. High-precision exploration and evaluation of marine gas hydrate still face great challenges as it is affected by the complex reservoir control mechanisms and distribution characteristics. Resistivity is widely used in geophysical logging and theoretical research on gas hydrate-bearing reservoirs by utilizing the high sensitivity electrical response. In this paper, based on the examination of the global marine gas hydrate occurrences, resistivity logging results are summarized. Then the key remaining gas hydrate resistivity experimental concerns are reviewed. In summary, resistivity properties are a reliable means to derive the gas hydrate reservoir characteristics, despite the effect induced by the anisotropic properties of hydrate reservoirs and drilling technology. The overall resistivity change associated with the occurrence of pore filling gas hydrate in reservoirs are relatively small, and the specific value is affected by sediment lithology and hydrate saturation. On the other hand, fracture filling hydrate reservoirs have strong anisotropy, and massive hydrate occurrences (i.e., layers of gas hydrate with no sediment) section shows very high resistivity variation. Clay minerals are an important factor restricting the accurate estimation of gas hydrate saturations from in situ resistivity measurements. Many experimental studies have proposed the correction of Archie empirical formula, but widely representative models have not yet been developed. It is worth noting that more complex resistivity measurements may be able to provide additional electrical response information on various gas hydrate systems.

Autophagy of hepatic stellate cell induced by Clonorchis sinensis - Bao Zheng; Zhiyan Gao; Liumei Liang; Yunyu Lu; Yongting Kong; Wanting Chen; Keying Lin; Wanqi Chen; Jingying Mai; Yanwen Li; Changling Ma (Molecular Biology Reports, 2022)

Pore-Scale Investigation of the Electrical Property and Saturation Exponent of Archie’s Law in Hydrate-Bearing Sediments - Jinhuan Zhao; Changling Liu; Chengfeng Li; Yongchao Zhang; Qingtao Bu; Nengyou Wu; Yang Liu; Qiang Chen (Journal of Marine Science and Engineering, 2022)
Characterizing the electrical property of hydrate-bearing sediments is essential for hydrate reservoir identification and saturation evaluation. As the major contributor to electrical conductivity, pore water is a key factor in characterizing the electrical properties of hydrate-bearing sediments. The objective of this study is to clarify the effect of hydrates on pore water and the relationship between pore water characteristics and the saturation exponent of Archie’s law in hydrate-bearing sediments. A combination of X-ray computed tomography and resistivity measurement technology is used to derive the three-dimensional spatial structure and resistivity of hydrate-bearing sediments simultaneously, which is helpful to characterize pore water and investigate the saturation exponent of Archie’s law at the micro-scale. The results show that the resistivity of hydrate-bearing sediments is controlled by changes in pore water distribution and connectivity caused by hydrate formation. With the increase of hydrate saturation, pore water connectivity decreases, but the average coordination number and tortuosity increase due to much smaller and more tortuous throats of pore water divided by hydrate particles. It is also found that the saturation exponent of Archie’s law is controlled by the distribution and connectivity of pore water. As the parameters of connected pore water (e.g., porosity, water saturation) decrease, the saturation exponent decreases. At a low hydrate-saturation stage, the saturation exponent of Archie’s law changes obviously due to the complicated pore structure of hydrate-bearing sediments. A new logarithmic relationship between the saturation exponent of Archie’s law and the tortuosity of pore water is proposed which helps to calculate field hydrate saturation using resistivity logging data.

Active Methanotrophs and Their Response to Temperature in Marine Environments: An Experimental Study - Jing Li; Xiaoqing Xu; Changling Liu; Nengyou Wu; Zhilei Sun; Xingliang He; Ye Chen (Journal of Marine Science and Engineering, 2021)
Aerobic methane (CH4) oxidation plays a significant role in marine CH4 consumption. Temperature changes resulting from, for example, global warming, have been suggested to be able to influence methanotrophic communities and their CH4 oxidation capacity. However, exact knowledge regarding temperature controls on marine aerobic methane oxidation is still missing. In this study, CH4 consumption and the methanotrophic community structure were investigated by incubating sediments from shallow (Bohai Bay) and deep marine environments (East China Sea) at 4, 15, and 28 °C for up to 250 days. The results show that the abundance of the methanotrophic population, dominated by the family Methylococcaceae (type I methanotrophs), was significantly elevated after all incubations and that aerobic methane oxidation for both areas had a strong temperature sensitivity. A positive correlation between the CH4 oxidation rate and temperature was witnessed in the Bohai Bay incubations, whereas for the East China Sea incubations, the optimum temperature was 15 °C. The systematic variations of pmoA OTUs between the Bohai Bay and East China Sea incubations indicated that the exact behaviors of CH4 oxidation rates with temperature are related to the different methanotrophic community structures in shallow and deep seas. These results are of great significance for quantitatively evaluating the biodegradability of CH4 in different marine environments.

The Variation of Microbial (Methanotroph) Communities in Marine Sediments Due to Aerobic Oxidation of Hydrocarbons - Jing Li; Changling Liu; Nengyou Wu; Xingliang He; Xiluo Hao; Feng Li; Ye Chen; Qingguo Meng (Journal of Ocean University of China, 2021)

Complete Genome Sequence Analysis of Brevibacillus laterosporus Bl-zj Reflects its Potential Algicidal Response - Yulei Zhang; Dong Chen; Jian Cai; Ning Zhang; Feng Li; Changling Li; Xianghu Huang (Current Microbiology, 2021)

Effect of Methane Gas on Acoustic Characteristics of Hydrate-Bearing Sediment-Model Analysis and Experimental Verification - Qingtao Bu; Gaowei Hu; Changling Liu; Jie Dong; Tongju Xing; Jianye Sun; Chengfeng Li; Qingguo Meng (Journal of Ocean University of China, 2021)

Nitrogen fixation driven by mesoscale eddies and the Kuroshio Current in the northern South China Sea and the East China Sea - Liuyang Li; Chao Wu; Jun Sun; Shuqun Song; Changling Ding; Danyue Huang; Laxman Pujari (Acta Oceanologica Sinica, 2020)

Phylogeny and Evolution of Calcineurin B-Like (CBL) Gene Family in Grass and Functional Analyses of Rice CBLs - Min Jiang; Changling Zhao; Mingfu Zhao; Yongzhong Li; Guosong Wen (Journal of Plant Biology, 2020)

Study of the Surface Morphology of Gas Hydrate - Jianye Sun; Chengfeng Li; Xiluo Hao; Changling Liu; Qiang Chen; Daigang Wang (Journal of Ocean University of China, 2020)

Mechanical Properties of Methane Hydrate-Bearing Interlayered Sediments - Lin Dong; Yanlong Li; Changling Liu; Hualin Liao; Guoqi Chen; Qiang Chen; Lele Liu; Gaowei Hu (Journal of Ocean University of China, 2019)

Effect of diet on the development, survival, and reproduction of the calanoid copepod Pseudodiaptomus dubia - Xiaoxia Luo; Changling Li; Xianghu Huang (Journal of Oceanology and Limnology, 2019)

Late onsets of tropical cyclones in the decaying years of super El Niño events - Zhiqiang Li; Runyu Zhang; Kai Liu; Changling Zheng; Zhikun Chen (Acta Oceanologica Sinica, 2019)

How root traits would be affected by soybean yield improvement? An examination of historical cultivars grafted with record-yield cultivar scion - Shengyou Li; Wenbin Wang; Yongqiang Cao; Changling Wang; Chunjuan Yan; Lijie Dong; Lishi Wu; Futi Xie; Shuhong Song (Plant and Soil, 2019)

Undrained shear strength evaluation for hydrate-bearing sediment overlying strata in the Shenhu area, northern South China Sea - Yanlong Li; Gaowei Hu; Nengyou Wu; Changling Liu; Qiang Chen; Chen’an Li (Acta Oceanologica Sinica, 2019)

Uptake of Urea Nitrogen by Oocystis borgei in Prawn (Litopenaeus vannamei) Aquaculture Ponds - Mei Liu; Xianghu Huang; Rui Zhang; Changling Li; Binhe Gu (Bulletin of Environmental Contamination and Toxicology, 2018)

Genome-wide association study dissects yield components associated with low-phosphorus stress tolerance in maize - Cheng Xu; Hongwei Zhang; Jianhao Sun; Zifeng Guo; Cheng Zou; Wen-Xue Li; Chuanxiao Xie; Changling Huang; Ruineng Xu; Hong Liao; Jinxiang Wang; Xiaojie Xu; et al. (Theoretical and Applied Genetics, 2018)

Effect of pure microcystin-LR on activity and transcript level of immune-related enzymes in the white shrimp (Litopenaeus vannamei) - Yanyan Chen; Xianghu Huang; Jianzhu Wang; Changling Li (Ecotoxicology, 2017)

Influence of foraminifera on formation and occurrence characteristics of natural gas hydrates in fine-grained sediments from Shenhu area, South China Sea - ChengFeng Li; GaoWei Hu; Wei Zhang; YuGuang Ye; ChangLing Liu; Qing Li; JianYe Sun (Science China Earth Sciences, 2016)

Baseline sensitivity of natural population and resistance risk of Peronophythora litchii to four novel QoI fungicides - Yuxin Zhou; Lei Chen; Jian Hu; Pengfei Liu; Yu Zhang; Qingxiao Meng; Bin Li; Naiguo Si; Changling Liu; Xili Liu (European Journal of Plant Pathology, 2016)

SolidEarth: a new Digital Earth system for the modeling and visualization of the whole Earth space - Liangfeng Zhu; Jianzhong Sun; Changling Li; Bing Zhang (Frontiers of Earth Science, 2014)